TRANSITION TO A COMMON 20kV DISTRIBUTION NETWORK - Crnković, Damir; Hederić, Željko; Hadžiselimović, Miralem (Journal of Energy Technology, 2024)
The aim of this paper is to review the basics of operation and planning problems of electric power systems with optimization techniques, considering the example of beginning the development of a new 20 kV distribution power network and its main constraints. The future network development of the power distribution network envisages a transition from 10 kV and 35 kV voltage levels to the 20 kV voltage level. This transition requires the building of a completely new 20(10) kV distribution network. This can be achieved by reconstructing the existing 10 kV power network into 10(20) kV network, which will then continue to operate at 10 kV voltage for some time, and by building a 20 kV power connection for new consumers with power value more than 1 (one) MVA.